Abnormal pigmentation within cutaneous scars: A complication of wound healing - Sarah Chadwick; Rebecca Heath; Mamta Shah (Indian Journal of Plastic Surgery)
Abnormally pigmented scars are an undesirable consequence of cutaneous wound healing and are a complication every single individual worldwide is at risk of. They present a challenge for clinicians, as there are currently no definitive treatment options available, and render scars much more noticeable making them highly distressing for patients. Despite extensive research into both wound healing and the pigment cell, there remains a scarcity of knowledge surrounding the repigmentation of cutaneous scars. Pigment production is complex and under the control of many extrinsic and intrinsic factors and patterns of scar repigmentation are unpredictable. This article gives an overview of human skin pigmentation, repigmentation following wounding and current treatment options.